Control of Hetero-Diels–Alder Stereoselectivity through Solvent Polarity and Brønsted or Lewis Acid Catalysis; Theory and Experiment - Loiseleur, Olivier; Cassayre, Jérôme; Leca, Dominique; Gaggini, Francesca; Pieniazek, Susan N.; Luft, Jennifer A. R.; Houk, Kendall N. (Synlett, 2013)
The stereoselectivity of cycloadditions involving 3-methyleneoxindole and 2-azadienes can be controlled by solvent polarity and by Lewis or Brønsted acid catalysis. The improvements in selectivity are advantageous for the synthesis of spiroquinazoline alkaloids such as alantrypinone and lapatin B.
Keywords: spiroquinazoline alkaloids; stereoselectivity; Lewis acid catalysis; hetero-Diels–Alder; natural products